ESRA19-0218 'Fast-track' patients to phase II recovery and decrease pacu duration in ambulatory arthroscopic shoulder surgery with combined peripheral nerve block and monitored anesthesia care. (30th August 2019) - Treanor, N; Vezina, V; Lui, A
Abstract : Background and aims: An estimated 460, 000 rotator cuff surgeries are performed in the United States annually. 1 We commonly perform these ambulatory arthroscopic shoulder surgeries (AASS) using a combination of an Interscalene block and superficial cervical plexus block under monitored anesthesia care (MAC). Our objective was to investigate how a change in anesthesia practice for AASS has impacted on the duration of PACU stay, and the ability to 'fast-track' patients to Phase II recovery, directly from the operating room. Methods: A 6-year retrospective electronic chart review was performed (OHSN-REB ethical approval) including all AASS at the Riverside Campus, the Ottawa Hospital from 01 January 2012 to 31 December 2107. Data were collected on type of anesthesia; general anesthesia (GA), GA and peripheral nerve block (PNB) or MAC and PNB, Phase I recovery duration (PACU) and the number of direct admissions to Phase II recovery. Results: 882 AASSs were performed in total from 2012 to 2017 (figure 1). the number of surgeries performed under MAC and PNB increased each year from 4 in 2012 to 195 in 2017. the direct admission rate to Phase II recovery increased from 0 in 2012 to 85 in 2017 (figure 2). the Phase I recovery (PACU) duration decreased from 72 minutes in 2012 to 41 minutes in 2017 (figure 3). Conclusions: This retrospective data collected, demonstrated how a change in anesthesia practice from GA and PNB to MAC and PNB reduced Phase I recovery duration and increased direct admission rate to Phase II recovery.